Rose Petal (Rosa indica) Extract as a Natural Antibacterial and Antifungal Agent against Oral Microbes - An In vitro Study - Swetha R; Shobana R; Sunayana M; Prabu D; Raj Mohan; Naveen Raj (Microbiology and Biotechnology Research: An Overview Vol. 3, 2025)
Introduction: Development of antibacterial agents aggravates the emerging antibiotic resistance; much attention has to be paid to natural produts. Nature has gifted with many herbs that have been found to have bactericidal and fungicidal action and these have been used from ages. One among them is Rose(rosaindica) which is easily available everywhere like other herbs. Many diseases of oral cavity are bacterial and fungal, especially all the immune compromised patients are affected with fungal and bacterial infections. Use of synthetic drugs may result in side effects and antibiotic resistance. So, the present study is all about determining the antibacterial and antifungal effect of rose. Hence, determining its application in dentistry, these can be used as an alternate to synthetic drugs to cure diseases. Material and Methods: Oral bacteria like Streptococcus mutans and Lactobacillus, the main microorganisms implicated in the initiation and progression of caries, were selected for the study. Petals of Rosa indica were used for the preparation of ethanolic extract. 100 g of the powdered sample were soaked in 300 ml of Ethanol in a soxhlet apparatus. The sample obtained from the soxhlet apparatus was then dissolved in (dimethyl sulfoxide) DMSO. This is used to detect Antimicrobial activity of Rosa indica. Both zone of inhibition and minimum inhibitory concentration (MIC) were evaluated using Agar well diffusion method and micro-dilution method respectively. The results thus obtained were then compared with the control against Streptococcus mutans and Candida albicans. Results: Zone of inhibition of rose extract was found to be 18 mm, 16 mm, 10 mm at 1000 \(μ\)g, 500 \(μ\)g, 250 \(μ\)g against Streptococcus mutans, which was less than the control kanamycin (24 mm) and zone of inhibition was 26 mm, 24 mm, 22 mm at 1000 \(μ\)g, 500 \(μ\)g, 250 \(μ\)g against Candida albicans which was greater than the control ketaconozole (19 mm). Thus, the rose extract has both antibacterial and antifungal property. Antifungal effect is more than antibacterial effect of rose. Discussion: Zone of inhibition of rose extract is more when compared to ketaconozole, an antifungal drug and less than kanamycin, an antibiotic drug. Rose extract has both antibacterial and antifungal property. Antifungal effect of rose is more than antibacterial effect and it is very effective against fungal diseases. Conclusion: We can state that roses have both antibacterial and antifungal activity. In the present study rose extract has more antifungal property than antibacterial property. Extract of rosaindica has promising effect in curing fungal diseases mainly in opportunistic infections of immunocompromised patients. This study adds knowledge encouraging the integration of traditional herbal remedies in modern clinical practice